2018
DOI: 10.3390/cancers10100380
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Thrombosis: An Overview of Mechanisms, Risk Factors, and Treatment

Abstract: Cancer-associated thrombosis is a major cause of mortality in cancer patients, the most common type being venous thromboembolism (VTE). Several risk factors for developing VTE also coexist with cancer patients, such as chemotherapy and immobilisation, contributing to the increased risk cancer patients have of developing VTE compared with non-cancer patients. Cancer cells are capable of activating the coagulation cascade and other prothrombotic properties of host cells, and many anticancer treatments themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
326
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(393 citation statements)
references
References 159 publications
7
326
3
3
Order By: Relevance
“…VTE is the second cause of mortality in patients with gynecologic cancer, and it has been reported that the risk of DVT and the incidence of PE were estimated at 17-40% and 1-26% in women undergoing gynecologic surgery [9,32].…”
Section: Discussionmentioning
confidence: 99%
“…VTE is the second cause of mortality in patients with gynecologic cancer, and it has been reported that the risk of DVT and the incidence of PE were estimated at 17-40% and 1-26% in women undergoing gynecologic surgery [9,32].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between cancer and venous thromboembolism (VTE) was first reported in 1865 by Armand Trousseau [15]. In general, active cancer is considered to increase the risk of PTE by 4-7 times [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…PDW is accepted as a more specific marker of platelet activation because it does not increase in response to platelet swelling. There are some studies in the literature regarding the relationship of PDW with PTE [15,26]. Sevuk et al reported that PDW values were higher in patients who developed acute PTE after DVT than those who did not [27].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is also associated with thrombotic complications [3]. The elevated risk is attributed to the high metastatic rate and the ability of pancreatic cancer cells to activate platelets and the coagulation cascade [4]. The current standard of care for PDAC includes gemcitabine as a single agent or in combination with nab-paclitaxel.…”
Section: Introductionmentioning
confidence: 99%